Volumetric polymerization shrinkage of contemporary composite resins - Halim Nagem Filho; Haline Drumond Nagem; Paulo Afonso Silveira Francisconi; Eduardo Batista Franco; Rafael Francisco Lia Mondelli; Kennedy Queiroz Coutinho (University of São Paulo, 2007)
The polymerization shrinkage of composite resins may affect negatively the clinical outcome of the restoration. Extensive research has been carried out to develop new formulations of composite resins in order to provide good handling characteristics and some dimensional stability during polymerization. The purpose of this study was to analyze, in vitro, the magnitude of the volumetric polymerization shrinkage of 7 contemporary composite resins (Definite, Suprafill, SureFil, Filtek Z250, Fill Magic, Alert, and Solitaire) to determine whether there are differences among these materials. The tests were conducted with precision of 0.1 mg. The volumetric shrinkage was measured by hydrostatic weighing before and after polymerization and calculated by known mathematical equations. One-way ANOVA (a or = 0.05) was used to determine statistically significant differences in volumetric shrinkage among the tested composite resins. Suprafill (1.87±0.01) and Definite (1.89±0.01) shrank significantly less than the other composite resins. SureFil (2.01±0.06), Filtek Z250 (1.99±0.03), and Fill Magic (2.02±0.02) presented intermediate levels of polymerization shrinkage. Alert and Solitaire presented the highest degree of polymerization shrinkage. Knowing the polymerization shrinkage rates of the commercially available composite resins, the dentist would be able to choose between using composite resins with lower polymerization shrinkage rates or adopting technical or operational procedures to minimize the adverse effects deriving from resin contraction during light-activation.